Product Differentiation and Oligopoly: A Network Approach - Bruno Pellegrino (Center for Economic Studies and ifo Institute (CESifo), 2023)
This paper develops a theory of oligopoly and markups in general equilibrium. Firms compete in a network of product market rivalries that emerges endogenously out of the characteristics of the products and services they supply. My model embeds a novel, highly tractable and scalable demand system (GHL) that can be estimated for the universe of public corporations in the USA, using publicly-available data. Using the model, I compute firm-level markups and decompose them into: 1) a new measure of firm productivity that accounts for product quality; 2) a metric of network centrality, which captures the extent of competition from substitute products. I estimate that, in 2019, public corporations produced consumer surplus in excess of 10 US trillions (against 3 trillions of profits). Oligopoly lowers total surplus by 11.5% and depresses consumer surplus by 31%. My analysis also suggests that both numbers were significantly lower in the mid-90s (7.9% and 21.5%, respectively). These results should be interpreted with care due to data limitations.
Keywords: D20; D40; D60; E20; L10; O40; 330; competition; concentration; general equilibrium; market power; markups; mergers; monopoly; networks; oligopoly; text analysis